2017
DOI: 10.1080/14737167.2017.1360767
|View full text |Cite
|
Sign up to set email alerts
|

Economic evaluation of outpatient parenteral antimicrobial therapy: a systematic review

Abstract: Outpatient parenteral antimicrobial therapy (OPAT) consists of providing antimicrobial therapy by parenteral infusion without hospitalization. A systematic review was performed to compare OPAT and hospitalization as health care modalities from an economic perspective. Areas covered: We identified 1455 articles using 13 electronic databases and manual searches. Two independent reviewers identified 35 studies conducted between 1978 and 2016. We observed high heterogeneity in the following: countries, infection s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…Previous economic evaluations of pediatric OPAT have been focused on comparisons between OPAT and prolonged hospitalization. 2,20 A recent systematic review revealed that OPAT was associated with substantial cost savings compared with prolonged hospitalization across all studies analyzed, with the cost of OPAT treatment courses ranging from $1000 to .$20 000. 2 The primary economic outcome in our study was the daily cost of medication administration, which was $65 for OPAT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous economic evaluations of pediatric OPAT have been focused on comparisons between OPAT and prolonged hospitalization. 2,20 A recent systematic review revealed that OPAT was associated with substantial cost savings compared with prolonged hospitalization across all studies analyzed, with the cost of OPAT treatment courses ranging from $1000 to .$20 000. 2 The primary economic outcome in our study was the daily cost of medication administration, which was $65 for OPAT.…”
Section: Discussionmentioning
confidence: 99%
“…19 Existing economic evaluations of pediatric OPAT are limited by small sample sizes, and indirect costs or caregiver QoL has not been assessed in studies. 2,20 Additionally, although there has been substantial research in which clinical outcomes between oral antimicrobial therapy and OPAT are compared, 8-10,12 there are no economic evaluations in which these 2 treatment modalities are compared. Our objective for this study was to compare the economic burden, including direct and indirect costs, and caregiver QoL between OPAT and oral antimicrobial therapy for children with serious infections requiring prolonged home treatment.…”
mentioning
confidence: 99%
“…permits reallocation of beds to other patients in need, reducing wait times and indirectly generating savings. 7,20,21 Despite being a new program in the hospital, the Antibiotic Clinic provided a high number of treatments and experienced significant growth in its second year. The dropout rate was a mere 1.6%.…”
Section: Antimicrobial Treatmentmentioning
confidence: 99%
“…This partly reflects a turn to more home-based and family-centred care across health services [6]. It also a reflects other policies such as reducing the length and number of inpatient stays, a belief that OPAT is a more cost-effective option when compared to continued inpatient care [7][8][9] and it may reduce healthcare-associated infections [1]. However, OPAT is not without risk [10] and a systematic review concludes further improvements in paediatric OPAT are needed for safe and effective implementation [4].…”
Section: Introductionmentioning
confidence: 99%